Effectiveness of using avatar-based technology in patient education for the improvement of chronic disease knowledge and self-care behavior: a systematic review protocol. (September 2016) - Wonggom, Parichat; Tongpeth, Jintana; Newman, Peter; Du, HuiYun; Clark, Robyn
Abstract : Review question/objective: The objective of this review is to investigate the effectiveness of using avatar-based technology in patient education for the improvement of knowledge and self-care behaviors for chronic disease.